INFLUENCE OF TEACHING METHODS ON DEAF STUDENTS’ ACADEMIC PERFORMANCE IN SCIENCES AT NGALA SCHOOL FOR THE DEAF, NAKURU COUNTY, KENYA - Okeng’o, Geoffrey Mienda; Okioma, Dr. Lazarus Momanyi (IJRDO- Journal of Educational Research, 2020)
The study sought to analyze teaching methods being used in class on deaf students’ performance in sciences at Ngala Secondary Schools for the Deaf in Nakuru County, Kenya. The study used a descriptive case study design. The target population is 1 principal, 21 teachers, and 450 students of Ngala secondary school of the deaf. The sample size of the study comprised of; 1 principal, 5 science teachers and 153 students producing a sample of 159 participants. Data was collected using questionnaires, interview and lesson observation. It was analyzed by both quantitative and qualitative data collection strategies. The quantitative data was presented using percentages, frequency tables and charts while data from principal, teachers, students and lesson observation will be reported in narrative form based on major themes.  The study found that majority of the teacher use learner centered teaching method as the best method in sciences. The study concluded that the most commonly used method of instruction is learner centered teaching method. The study recommended that the Ministry of Education Science and Technology (MoEST) in conjunction with Quality Assurance and Standard Officers (QUASO) should intensify inspection of schools for the deaf to ensure that teachers were using correct teaching methods that allowed learners to occupy an active role in the learning environment.